Teacher Personality Competence According to KH. Ahmad Dahlan and Ki Hadjar Dewantara: a Comparative Study - Syahrul, Syahrul; Saefuddin, Didin; Bahruddin, E.; Husaini, Adian; Raharjo, Arif Budi (Formosa Journal of Applied Sciences, 2024)
A personality that is religious, mature, stable, diligent and so on will have a great influence on the educational process and in shaping the soul of students. Because the teacher is a figure who must be able to hear his words and exemplify his behavior. As educational figures as well as teachers, both KH Ahmad Dahlan and Ki Hadjar Dewantara paid great attention to the personality of teachers. Both established special educational institutions for teacher regeneration. By using library research as a data collection technique and with a historical approach, this research concludes that the teacher's personality competence according to KH Ahmad Dahlan is shown by the attitude of having the right faith, being sincere in educating, being humble, always purifying oneself (tazakiyah an-nafs), and having the courage to make sacrifices.